Ad Hoc Influenza Vaccination During Years of Significant Antigenic Drift in a Tropical City With 2 Seasonal Peaks: A Cross-Sectional Survey Among Health Care Practitioners. Issue 19 (May 2016) - Wong, Martin C.S.; Nelson, E. Anthony S.; Leung, Czarina; Lee, Nelson; Chan, Martin C.W.; Choi, Kin Wing; Rainer, Timothy H.; Cheng, Frankie W.T.; Wong, Samuel Y.S.; Lai, Christopher K.C.; Lam, Bosco; Cheung, Tak Hong; et al.
Abstract : Abstract: We evaluated the acceptability of an additional ad hoc influenza vaccination among the health care professionals following seasons with significant antigenic drift. Self-administered, anonymous surveys were performed by hard copy questionnaires in public hospitals, and by an on-line platform available to all healthcare professionals, from April 1st to May 31st, 2015. A total of 1290 healthcare professionals completed the questionnaires, including doctors, nurses, and allied health professionals working in both the public and private systems. Only 31.8% of participating respondents expressed an intention to receive the additional vaccine, despite that the majority of them agreed or strongly agreed that it would bring benefit to the community (88.9%), save lives (86.7%), reduce medical expenses (76.3%), satisfy public expectation (82.8%), and increase awareness of vaccination (86.1%). However, a significant proportion expressed concern that the vaccine could disturb the normal immunization schedule (45.5%); felt uncertain what to do in the next vaccination round (66.0%); perceived that the summer peak might not occur (48.2%); and believed that the summer peak might not be of the same virus (83.5%). Furthermore, 27.8% of all respondents expected that the additional vaccination could weaken the efficacy of previous vaccinations; 51.3% was concerned about side effects; and 61.3% estimated that there would be a low uptake rate. If the supply of vaccine was limited, higher priority groups were considered to include the elderly aged ≥65 years with chronic medical conditions (89.2%), the elderly living in residential care homes (87.4%), and long-stay residents of institutions for the disabled (80.7%). The strongest factors associated with accepting the additional vaccine included immunization with influenza vaccines in the past 3 years, higher perceived risk of contracting influenza, and higher perceived severity of the disease impact. The acceptability to an additional ad hoc influenza vaccination was low among healthcare professionals. This could have a negative impact on such additional vaccination campaigns since healthcare professionals are a key driver for vaccine acceptance. The discordance in perceived risk and acceptance of vaccination regarding self versus public deserves further evaluation.